Fatigue crack growth determination under in-phase and out-of-phase mixed-mode loading conditions using an automated DIC evaluation tool. (November 2022) - Panwitt, Hannes; Köster, Paul; Sander, Manuela
Highlights: Further development of a tool for automated crack detection on the basis of DIC data. Determination of complex crack paths under spatial mixed mode loading conditions. New method for assignment of load cycle numbers to branching fatigue cracks length. Validation of the new tool for in-phase and out-of-phase loading conditions. Abstract: In this study Digital Image Correlation (DIC) is utilized for measuring complex fatigue crack paths under spatial mixed-mode loading conditions. Therefore, an existing automated script was extended by two criteria for measuring the crack length versus the number of load cycles. Experimental investigations were conducted under mode I conditions, to calibrate the new evaluation routine. Moreover, in-phase and out-of-phase mixed-mode experiments under superimposed tension-torsion loading were performed to validate the method. The results show that the newly presented procedure provides an accurate, automated evaluation tool for mixed-mode fatigue crack growth tests, independent of the crack orientation and possible branching.